Genome Sequences of Two Dual-Serotype-Specific Echovirus 20 Strains from Nigeria (2020)
Here, we describe nearly complete genome sequences (7,361 nucleotides [nt] and 6,893 nt) of two echovirus 20 (E20) isolates from Nigeria that were simultaneously typed as CVB and E20 (dual serotype) by neutralization assay. Both include two overlapping open reading frames (ORFs) of 67 and 2,183 amino acids that encoded a recently described gut infection-facilitating protein and the classic enterovirus proteins, respectively.